Determination of Chlorophyll Levels of Water Kale Plants (Ipomoea aquatica Forkss) Experiencing Nutrient Deficiencies - Sumiati; M. Fatih Salsabila; Akmal Surur (Jurnal Biologi Tropis, 2023)
The effect of nutrient deficiency on plants can cause a decrease in plant growth and productivity. The decrease in biomass production is related to the decrease in photosynthesis rate caused by the inhibition of chlorophyll synthesis process. This study aims to determine the chlorophyll content of kale (Ipomoea aquatica) that experienced nutrient deficiencies. The type of research used is an experiment using a completely randomized design (CRD) with three replications. The treatment given was the provision of nutrient solutions: complete, -Ca, -S, -Mg, -K, -N, -P, Fe, -Micronutrients, distilled water and water. The solvent used for maceration was DMSO. The parameters observed were chlorophyll a, chlorophyll b and total chlorophyll content of kale leaves. The results showed that the complete solution had the highest total chlorophyll content of 6.387 mg/L. While the distilled water solution has the lowest total chlorophyll content of 2.982 mg/L. The complete solution has all the nutrients needed by plants so that the growth and development process can run optimally, characterized by high chlorophyll content.